The Marketing Mix and Service Quality in Relation to Their Impacts on Customer Satisfaction: A Study of Fast Food Chains in Taiwan - Huang, Liang-Chin (2006)
The major objective of this dissertation is to explore the relationship between marketing mix/service quality and customer satisfaction in fast food chains in Taiwan. A mathematical relationship was sought to identify whether (a) marketing strategies developed from 4P (product, price, promotion and place) are related to customer satisfaction. (b) service quality developed from DINESERV (Stevens, Knutson, and Patton, 1995), the restaurant service quality measuring tool, is related to customer satisfaction, and (c) consumer satisfaction towards marketing and service of fast food chains differ by gender, age, education, occupation and income groups.